Factors Affecting Late Introduction of Complementary Food: A Kaplan Meier Analysis - V M Holambe; N A Thakur (Medsci Publications, 2014)
Introduction: Late introduction of complementary food is associated with malnutrition and in India about 47% of children are given complementary food at age ≥6 months. The present study was conducted to estimate the age at introduction of complementary food and factors affecting it. Aim and objectives: To estimate the age at introduction of complementary food and some socio-demographic and reproductive factors affecting it by Kaplan-Meier survival analysis. Methodology: This was a cross sectional study conducted in Government Medical College, Latur (Maharashtra, India) during 1stMay 2013 to 30thJune 2013. The study population consisted of 197 mother-infant pairs attending the Immunization Clinic. Data was collected by direct interview using predesigned and pretested questionnaire. The data was analyzed using Kaplan Meier procedure. Informed consent was taken from all the study subjects. Results: Out of the 69 infants in whom complementary food was introduced, 32(46.38%) were given it at appropriate age and 37 (53.62%) were late. Age of mother, parity and education of mother were significantly associated with delayed introduction of complementary food. Conclusion: There was a definite delay in starting complementary feeding. Late introduction of complementary food is associated with maternal age, education and parity.